Respostas
respondido por:
9
dados :
>>>>>>>
a1 = 3
a2 = 7
r = a2 - a1 ---> r = 7 - 3 ---> r = 4
Formula dao termo P.A
=====================
an = a1 + ( n - 1 ) x r
an = 3 + ( n - 1 ) x 4
an = 3 + 4n - 4
an = 4n - 4 + 3
an = 4n - 1
>>>>>>>
a1 = 3
a2 = 7
r = a2 - a1 ---> r = 7 - 3 ---> r = 4
Formula dao termo P.A
=====================
an = a1 + ( n - 1 ) x r
an = 3 + ( n - 1 ) x 4
an = 3 + 4n - 4
an = 4n - 4 + 3
an = 4n - 1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás